Bad, bad Seymour Brown - Isaacs, Susan, 1943- (Isaacs, Susan, 1943- Corie Geller novel., 2023)
"When Corie Geller asked her parents to move from their apartment into the suburban McMansion she shares with her husband and teenage daughter, she assumed they'd fit right in with the placid life she'd opted for when she left the Joint Terrorism Task Force of the FBI. But then her dad gets a call from genial and slightly nerdy film professor, April Brown--one of the victims of the case he was never able to solve. When April was five years old, she'd emerged unscathed from the arson that killed her parents. Now, two decades later, she's asking for help. Someone has made another attempt on her life. It takes only a nanosecond for Corie and her dad to say Absolutely! and kick off a full-fledged investigation. If they don't move fast, whoever attacked April is sure to strike again. But while her late father, Seymour Brown, was the go-to money launderer for the Russian mob--a brilliant, volatile, and violent man with a penchant for Swiss watches and cheating on his wife--April Brown has no enemies. Popular with her students, esteemed by colleagues, her only connection to crime is her passion for the noir movies of Hollywood's golden age. Who would want April dead now? And who set that horrific fire, all those years ago? The stakes have never been higher. Yet as Corie and her dad have come to understand, they still live for the chase."--